SURVEY MOTIVASI KERJA DRIVER OJEK ONLINE GRAB - Fitria Nur Anggraeni (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
It's not easy to get a job in this century, although highly educated, there is no guarantee. However, technological progress does not mean without opportunities, one of them being a transportation partner. Being a freelance worker is not as good as it seems, because the amount of income is very dependent on hard work, and it really drains everything. So it is not uncommon to feel tired and discouraged. Moreover, the field of work is very dependent on the customer, so there is not much to do but keep hoping for the opportunity. This study aims to find information about the work motivation of online drivers, the quantitative approach is expected to provide input. The population is determined by 50 respondents with an incidental sample technique. The results showed that the highest motivation for drivers was necessity, followed by hope. This finding confirms that the motivation theory initiated by Maslow is operationally very dependent on the characteristics of the research subjects, so the treatment will be different.